Crack mediated dislocation activities in Al/Ti nanolayered composites: an atomistic study. (1st December 2022) - Maurya, Sumit Kumar; Chandra, Sagar; Nie, Jian-Feng; Alankar, Alankar
Abstract: In this work, to understand crack propagation in Al/Ti nanolayered composites, a series of molecular dynamic simulations were performed with crack in different layers of the nanolayered composites and subjected to mode I loading. Nanolayered composite with a crack in Al layer, and monolithic Al show ductile fracture behavior that occurs by nucleation of Shockley partial dislocation at the crack tip. On the other hand, the fracture behavior in nanolayered composites with a crack in Ti shows crack bowing which is similar to the brittle fracture, and subsequent crack trapping at the interface. However, monolithic Ti shows typical cleavage fracture followed by activation of basal and pyramidal ⟨ c + a ⟩ slip that blunts the crack leading to ductile fracture. When the crack is in the Ti layer, the other Ti layers in a nanolayered composite deform by prismatic and pyramidal ⟨ c + a ⟩ slip. However, the Ti layer deforms only via slip on prismatic planes when the crack is in the Al layer. Critical strain energy release rate G c based continuum analysis predicts the fracture mode in monolithic Ti correctly, but it fails to predict the fracture mode in monolithic Al and nanolayered composites with crack in the Al layer. It is found that the G c determined based on external loading is marginally higher when the crack is in the Al layer as compared against the case when the crack is in the Ti layer. The G c value for the basal and pyramidal slip in Ti is higher than the G c value for cleavage. This poses an interesting phenomenon since the G c in monolithic Al is found to be much lower than that of monolithic Ti. The reason is attributed to the constrained plasticity in the presence of an Al/Ti interface.